Triterpene saponins from Eryngium kotschyi. (February 2015) - Aslan Erdem, Sinem; Mitaine-Offer, Anne-Claire; Miyamoto, Tomofumi; Kartal, Murat; Lacaille-Dubois, Marie-Aleth
Graphical abstract: Four oleanane-type saponins (1 –4 ) were isolated from the roots of Eryngium kotschyi . Their structures were established by extensive spectroscopic interpretation. Two of them possessed unusual structures: the aglycon of3 is a triacetylated derivative of oleanane-type skeleton with a ketone function at the C-16 position, and4 is a glycoside of a 17, 22-seco-oleanolic acid, which might be a chemotaxonomic marker of the Apiales order. Highlights: Four new oleanane-type saponins were isolated from the roots, two of them being unusual. Their structures were elucidated by extensive spectroscopic analyses. The 21, 22, 28- O -triacetylated olean-12-en-16-one as aglycone is characterized for the first time. The 17, 22-seco-oleanolic acid might be a chemotaxonomic marker of the Apiales order. Abstract: Four new oleanane-type saponins 3- O -α-l -rhamnopyranosyl-(1 → 4)-β-d -glucuronopyranosyl-22- O -β, β-dimethylacryloylA1-barrigenol (1 ), 3- O -α-l -rhamnopyranosyl-(1 → 4)-β-d -glucuronopyranosyl-22- O -angeloylA1-barrigenol (2 ), 3- O -β-d -glucopyranosyl-(1 → 2)-[β-d -glucopyranosyl-(1 → 6)]-β-d -glucopyranosyl-21, 22, 28- O -triacetyl-(3β, 21β, 22α)-olean-12-en-16-one (3 ), and 3- O -β-d -glucopyranosyl-(1 → 2)-glucopyranosyl-22- O -β-d -glucopyranosylsteganogenin (4 ), along with the known 3- O -β-d -galactopyranosyl-(1 → 2)-[α-l -arabinopyranosyl-(1 → 3)]-β-d -glucuronopyranosyl-22- O -angeloylA1-barrigenol and 3- O -α-l -rhamnopyranosyl-(1 → 4)-β-d -glucuronopyranosyloleanolic acid, were isolated from a methanol extract of the roots of Eryngium kotschyi by multiple chromatographic steps. Saponins3 and4 are unusual by the original structure of their aglycon. Compound3 possessed an oleanane-type skeleton with a 21, 22, 28-triacetylation and a ketone function at the C-16 position. For compound4, the 17, 22-seco-oleanolic acid skeleton is rarely found in natural saponins.